Availability and Management of Nitrogen in Soils of Arid Ecosystem - Aggarwal, R K; Kumar, Praveen (Annals of Arid Zone, 2016)
In this paper, the work on the availability of nitrogen and its management for sustainable production has been reviewed with particular reference to soils in arid ecosystem. The available literature on status of soil nitrogen, its succession and transformation under natural ecosystems suggest the variability in arid regions which are dependent on the soil climatic conditions. In Indian arid zone particularly western Rajasthan, the organic carbon and nitrogen are reported as low as 0.05% and 0.007% respectively in sand dunes, however, the stabilization of dunes with vegetation increases these contents albeit slowly. Amongst tree species, Prosopis cineraria has been found to be a soil fertility restorer. Compared to the figure of 4 kgN ha-1 annum-1 for Indian subcontinent, the precipitation in arid region of western Rajasthan brings about 6-10 kg N ha-1 annum-1, however in Negev desert of Israel, this value goes upto 20 kg N ha-1 annum-1. Amongst different pathways of N loss, NH3 volatilization is a major process operating in arid region. The ways to reduce such losses have been discussed, Use of on-farm organic residues and inclusion of legumes in crop rotation, are some of the management practices suggested which ensure importance for sustainable production, fertility maintenance and enhancing fertilizer N use efficiency in arid region.